2022
DOI: 10.3389/feart.2022.931340
|View full text |Cite
|
Sign up to set email alerts
|

A study on the effect of site response on California seismic hazard map assessment

Abstract: Prior studies have repeatedly shown that probabilistic seismic hazard maps from several different countries predict higher shaking than that observed. Previous map assessments have not, however, considered the influence of site response on hazard. Seismologists have long acknowledged the influence of near-surface geology, in particular low-impedance sediment layers, on earthquake ground-motion at frequencies of engineering concern. Although the overall effects of site response are complex, modern ground-motion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 41 publications
(41 reference statements)
0
2
0
Order By: Relevance
“…We investigated this question primarily using a dataset from the California Historical Intensity Mapping Project (CHIMP) ( 13 ) that we compiled, giving us full information about the data and thus the ability to conduct detailed analyses. First, we considered the influence of local geology on shaking and hazard via the commonly used proxy Vs30 (the time-averaged shear-wave velocity in the upper 30 m of the crust) and found that these site effects were not a substantial contributor to the observed discrepancy, as including them tended to increase the discrepancy by up to approximately 10% rather than decrease it ( 24 ). Next, we explored issues arising from different magnitudes of completeness between the data.…”
Section: Discussionmentioning
confidence: 99%
“…We investigated this question primarily using a dataset from the California Historical Intensity Mapping Project (CHIMP) ( 13 ) that we compiled, giving us full information about the data and thus the ability to conduct detailed analyses. First, we considered the influence of local geology on shaking and hazard via the commonly used proxy Vs30 (the time-averaged shear-wave velocity in the upper 30 m of the crust) and found that these site effects were not a substantial contributor to the observed discrepancy, as including them tended to increase the discrepancy by up to approximately 10% rather than decrease it ( 24 ). Next, we explored issues arising from different magnitudes of completeness between the data.…”
Section: Discussionmentioning
confidence: 99%
“…Site conditions play a decisive role in the influence of ground motion [1,2]. In engineering seismic design, the engineering design and construction solutions that are compatible with the characteristics of the site conditions can effectively reduce the damage to the engineering structure from seismic effects, extend its safe service life, and contribute to the sustainability of the engineering structure.…”
Section: Introductionmentioning
confidence: 99%